Kinetic probe to study the structure of micelles: effects of inert inorganic and organic salts on the rate of alkaline hydrolysis of phthalimide in the presence of cationic micelles - Khan, M.Niyaz; Ahmad, Faujan B.H. (Elsevier, 2001)
Pseudo-first-order rate constants (kobs) for the alkaline hydrolysis of phthalimide (PTH), obtained at a constant concentration of cetyltrimethylammonium bromide (CTABr) and 35°C, vary with the increase in the concentration of sodium phenylacetate and sodium sulfate (MX) according to the relationship: kobs=(k0+θK[MX])/(1+K[MX]) where θ and K are empirical parameters. The value of θ/khW (where khW=kobs at [CTABr]T=[MX]=0) is the measure of the extent of expulsion of ionized PTH (S-) from CTABr micellar pseudophase to aqueous pseudophase by an inert anion (X-) provided S- is fully micellized in the absence of X-. Thus, the values of θ/khW for sodium phenylacetate (≈1) and sodium sulfate (≈0.12-0.19) are attributed to deeper micellar penetration of S- and phenylacetate ions compared to that of sulfate ions. Copyright © 2001 Elsevier Science B.V.